While we were watching Downton Abbey - Wax, Wendy (Berkley Books, 2013)
"When the concierge of The Alexander, a historic Atlanta apartment building, invites his fellow residents to join him for weekly screenings of Downton Abbey, four very different people find themselves connecting with the addictive drama, and--even more unexpectedly--with each other." -- Cover flap.